Pengaruh Kinerja Lingkungan, Corporate Governance Pada Pengungkapan Corporate Social Responsibility - Wulan Rahmasari Gusti Ayu Putu (Fakultas Ekonomi Universitas Warmadewa, 2020)
This research examines the influence of environmental performance, institutional ownership, managerial ownership of corporate social responsibility disclosures by using mining companies incorporated in the Indonesia Stock Exchange (IDX) and also listed in PROPER. The sample meets the criteria of research is as much as 55 samples during the period of 2014-2018. The Data available is then processed using multiple regression analysis techniques. The results of the research were seen from the test value of T test that has been done and resulted in significant value that has been shown that environmental performance has an influence on CSR disclosure. Significant results are also obtained in managerial performance variables stating this variable affects CSR disclosures. While the institutional ownership variables have a significant value greater than 0.05 resulting from the outcome, institutional ownership is stated to have no effect on CSR disclosures. Keywords: environmental performance, institutional ownership, managerial ownership and corporate social responsibility disclosure